Single crystal, luminescent carbon nitride nanosheets formed by spontaneous dissolution - Miller,TS; Suter,TM; Telford,AM; Picco,L; Payton,OD; Russell-Pavier,F; Cullen,PL; Sella,A; Shaffer,MSP; Nelson,J; Tileli,V; McMillan,PF; et al. (Nano Letters, 2017)
A primary method for the production of 2D nanosheets is liquid-phase delamination from their 3D layered bulk analogues. Most strategies currently achieve this objective by significant mechanical energy input or chemical modification but these processes are detrimental to the structure and properties of the resulting 2D nanomaterials. Bulk poly(triazine imide) (PTI)-based carbon nitrides are layered materials with a high degree of crystalline order. Here, we demonstrate that these semiconductors are spontaneously soluble in select polar aprotic solvents, that is, without any chemical or physical intervention. In contrast to more aggressive exfoliation strategies, this thermodynamically driven dissolution process perfectly maintains the crystallographic form of the starting material, yielding solutions of defect-free, hexagonal 2D nanosheets with a well-defined size distribution. This pristine nanosheet structure results in narrow, excitation-wavelength-independent photoluminescence emission spectra. Furthermore, by controlling the aggregation state of the nanosheets, we demonstrate that the emission wavelengths can be tuned from narrow UV to broad-band white. This has potential applicability to a range of optoelectronic devices.